Constructing Religious Legitimacy through Religious Agency: The Restoration of the Theravāda Bhikkhunī Saṅgha in Indonesia - Putu Aryatama (Pustaka Peradaban, 2026)
The restoration of the Theravāda Bhikkhunī Saṅgha in Indonesia presents a compelling case of religious growth within an environment where institutional ordination remains contested. Drawing on a qualitative transcendental phenomenological design, this study examines how Indonesian Bhikkhunīs construct religious legitimacy through religious agency despite ongoing institutional contestation. Data were gathered through in-depth interviews, participant observation, and documentary analysis with Bhikkhunīs, lay supporters, and monastic authorities. The findings reveal that religious legitimacy is constructed across three interconnected dimensions of agency: (1) spiritual self-formation through embodied Vinaya discipline and ethical practice, which grounds moral credibility; (2) collective capacity building via Dhamma education, monastery development, and transnational networking, which expands social presence; and (3) relational authority negotiation through non-confrontational engagement, digital communication, and strategic alliances, which navigates structural barriers. Together, these practices demonstrate that legitimacy is not merely a status conferred by formal institutions, but a dynamic, bottom-up social process earned through daily practice and communal engagement. Conceptually, the study advances an agency-based framework of religious legitimacy, offering broader analytical insights for understanding how restored, emerging, or marginalized religious actors establish authority under structural constraints. Restorasi Saṅgha Bhikkhunī Theravāda di Indonesia menyajikan kasus pertumbuhan keagamaan yang menarik di dalam lingkungan tempat penahbisan institusional masih terkontestasi. Dengan menggunakan desain fenomenologi transendental kualitatif, penelitian ini menguji bagaimana para Bhikkhunī di Indonesia mengonstruksi legitimasi keagamaan melalui agensi keagamaan (religious agency) di tengah kontestasi institusional yang masih berlangsung. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan analisis dokumentasi bersama para Bhikkhunī, penyokong awam (lay supporters), serta otoritas monastik. Temuan penelitian mengungkapkan bahwa legitimasi keagamaan dikonstruksi melalui tiga dimensi agensi yang saling terhubung: (1) pembentukan diri secara spiritual (spiritual self-formation) melalui penghayatan disiplin Vinaya dan praktik etis, yang melandasi kredibilitas moral; (2) peningkatan kapasitas kolektif (collective capacity building) melalui pendidikan Dhamma, pembangunan vihara/biara, dan jaringan transnasional, yang memperluas kehadiran sosial; serta (3) negosiasi otoritas relasional (relational authority negotiation) melalui keterlibatan non-konfrontatif, komunikasi digital, dan aliansi strategis, yang menavigasi hambatan-hambatan struktural. Secara bersama-sama, praktik-praktik ini menunjukkan bahwa legitimasi bukanlah sekadar status yang diberikan oleh institusi formal, melainkan sebuah proses sosial dinamis dari bawah ke atas (bottom-up) yang diperoleh melalui praktik harian dan keterlibatan komunitas. Secara konseptual, penelitian ini memajukan kerangka kerja legitimasi keagamaan berbasis agensi (agency-based framework), yang menawarkan wawasan analitis lebih luas untuk memahami bagaimana aktor keagamaan yang dipulihkan, baru muncul, atau terpinggirkan membangun otoritas di bawah keterbatasan struktural.